STUDI LITERATUR : BIRTH BALL UNTUK INTENSITAS NYERI PERSALINAN KALA 1 - Ni Wayan Lasihati; I Komang Lindayani; Ni Gusti Kompiang Sriasih (Forind Press, 2026)
Labor pain arises from uterine contractions that push the baby's head, causing cervical dilation and effacement. If not managed effectively, labor pain can lead to complications such as prolonged labor. One therapeutic intervention for first-stage labor pain is the use of a birth ball-an inflatable rubber ball designed to help reduce labor pain. Research Objective: To examine the application of birth balls regarding pain intensity during the first stage of labor. This study employed a literature review method; the article selection process followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, comprising four stages: identification, screening, eligibility assessment, and inclusion. Articles were obtained by searching the Google Scholar database using the keywords